Community engagement approaches for malaria prevention, control and elimination: A scoping review protocol - Awasthi, Kiran; Jancey, Jonine; Clements, Archie C.A.; Leavy, Justine (2021)
Community engagement (CE) is important for malaria prevention, control and ultimately elimination. As the decline of malaria has plateaued over the last 5 years, strengthening CE approaches will be necessary to enhance health promotion practice and policy to drive malaria transmission down further. Countries have adopted a wide range of public health intervention approaches for malaria prevention and control that best suit their context. This review will examine the existing evidence on the various CE approaches adopted by malaria programmes across the world and their outcomes. Methodology and analysis The review methodology will follow the updated Joanna Briggs Institute guide for scoping review, 2017, which is based on the framework developed by Arksey and O'Malley and further developed by Levac Colquhoun and O'Brien. Proquest, Web of Knowledge and Medline will be searched for publications from January 2000 to 31 March 2021 while Google search engine will be used to find any grey literature. The eligibility criteria will be as follows: review will include primary studies written in the English language using appropriate study designs and methods, including quantitative, qualitative and mixed methods designs; and case, programme or project reports. Information on CE approaches designed specifically for malaria prevention, control, elimination and their outcomes will be explored. Subheadings and free text terms for € community engagement' and € malaria' will be used for the search. The article screening and data extraction will be examined by two reviewers after the initial search, and any disputes will be resolved by a third reviewer through discussion. The Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for scoping reviews guide will be used to present the review methods and the results from the search. The scoping review results will identify and map the available evidences, sources of information and research gaps in the area of CE as one approach for malaria prevention, control and/or elimination. Ethics and dissemination This study only aims to review secondary sources and does not require human research ethics committee approval. The findings of the scoping review will be submitted to a peer-reviewed journal for wider dissemination.